Association of Diabetes Mellitus with Acute Ischemic Stroke (Bangladesh Journal of Medical Biochemistry, 2018)
Acute ischemic stroke occurs more frequently in diabetic patients. The purpose of the present study was to observe the association of diabetes mellitus with acute ischemic stroke in Bangladeshi population. This case-control study was carried out in the Department of Biochemistry, Dhaka Medical College, Dhaka, Bangladesh during the period from January 2014 to December 2014. Patients presenting with acute ischemic stroke, age ranges from 18 to 65 years of both sexes, were taken as the case group. Age-and sex-matched healthy individuals were selected as control group. History of diabetes of both cases and controls were recorded and blood sample was collected from both cases and controls after overnight fasting for the estimation of blood sugar. A total number of 100 study subjects were taken of which 50 subjects presented with acute ischemic stroke were considered as cases and the rest 50 healthy subjects were taken as controls. In this study, the mean(±SD) of age of cases and controls were 56.54±12.18 and 53.34±7.98 years respectively. There was no statistically significant difference between mean age of the groups (p=0.124). Mean (±SD) of BMI was significantly higher in cases than that of controls (p=0.002) which were 27.25±3.25 and 25.38±2.57 respectively and the study subjects were sex matched, the difference between cases and controls was not statistically significant (p= 0.414). Diabetes mellitus was more commonly reported in case group (46.0%) than control group (6.0%) and the difference was found statistically significant (p=0.001). The risk estimation was calculated and was found a 13.34 OR (95% C.I. 3.66 to 48.62). From the findings of this study in may be concluded that diabetes mellitus is significantly associated with acute ischemic stroke.Bangladesh J Med Biochem 2016; 9(2): 45-48